Long-term results of a second-generation, small-diameter, metal-on-metal bearing in primary total hip arthroplasty at 14-year follow-up - Reiner, Tobias; Klotz, Matthias C. M.; Seelmann, Kirsten; Hertzsch, Fabian; Innmann, Moritz Maximilian; Streit, Marcus R.; Nees, Timo A.; Moradi, Babak; Merle, Christian; Kretzer, Jan Philippe; Gotterbarm, Tobias (Materials, 2020)
(1) Background: The objective of the present study was to review the clinical and radiological results of a small-head, MoM bearing in primary THA and to determine blood metal ion levels at long-term follow-up. (2) Methods: We retrospectively evaluated the clinical and radiological results of 284 small-diameter, MoM 28-mm Metasul THA at a mean follow-up of 14.5 years, and measured blood metal ion concentrations in 174 of these patients. (3) Results: After 14 years, survival free for revision due to any reason was 94%. Proximal femoral osteolysis was seen in 23% of hips, and MRI demonstrated ARMD in 27 of the 66 investigated hips (41%). Mean cobalt, chromium, and titanium ion concentrations were 0.82 µg/L (range 0.22-4.45), 1.51 µg/L (0.04-22.69), and 2.68 µg/L (0.26-19.56) in patients with unilateral THA, and 2.59 µg/L (0.43-24.75), 2.50 µg/L (0.26-16.75), and 3.76 µg/L (0.67-19.77), respectively in patients with bilateral THA. Twenty-nine percent of patients showed cobalt or chromium ion levels > 2 µg/L. (4) Conclusions: Despite good clinical long-term results, increased blood metal ion levels (cobalt or chromium > 2 µg/L) were found in approximately one-third of asymptomatic patients, and proximal femoral osteolysis and ARMD were frequently seen in this cohort. Blood metal ion analysis appears helpful in the long-term follow-up of these patients in order to identify individuals at risk. In accordance with contemporary consensus statements, symptomatic patients with elevated metal ion levels and/or progressive osteolysis should be considered for additional CT or MARS MRI to determine the extent of soft tissue affection prior to revision surgery. Further studies are necessary to investigate the clinical relevance of ARMD in asymptomatic patients with small-head, MoM THA.
Gesehen am 16.04.2020